The Analysis of Word Formation Processes in the Jakarta Post Website - Dian Luthfiyati; Abdul Kholiq; Intan Ni matus Zahroh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
A new language and term use new words that we can relate to the one of linguistics branches of the morphological aspect namely word formation process. The process of word formation in creation of new English words is called derivation. One of the language phenomenon is in the practice of language used in online news specifically Jakarta Post Website. The Jakarta Post is one of the daily Indonesian has language English. The Jakarta post presented with various of news, such as sport, entertainment, education, etc. The purpose of this study is identifying the most common type of derivation words that is used in the headline of ten education articles in Jakarta Post Website in October 2015 until April 2016. This study uses qualitative method. The result show that the most common of derivation words that is used in headline ten article educations in Jakarta Post Website in October 2015 until April 2016 is noun derivations. Keywords: derivation, Jakarta Post.